2017
DOI: 10.1111/petr.13041
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk organ transplantation in the pediatric population

Abstract: IRD organs are classified by the Public Health Service to be at above-average risk for harboring human immunodeficiency virus, hepatitis C, and hepatitis B. Traditionally underutilized, there exists even greater reluctance for their use in pediatric patients. We performed a retrospective analysis via the United Network for Organ Sharing database of all pediatric renal and hepatic transplants performed from 2004 to 2008 in the United States. Primary outcomes were patient and graft survival. Proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
2
5
1
Order By: Relevance
“…Therefore, patients and/or providers might be making a decision to wait for the “ideal donor” rather than using a donor labeled as increased risk that, in reality, has a very low risk of infectious transmission 16 . Previous studies have demonstrated equivalent outcomes to standard criteria organs with the use of livers from increased risk donors in adults and pediatrics 3,20 . In our analysis, we also demonstrated no difference in patient or allograft survival between recipients receiving PHS increased risk donors and non‐increased risk donors.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Therefore, patients and/or providers might be making a decision to wait for the “ideal donor” rather than using a donor labeled as increased risk that, in reality, has a very low risk of infectious transmission 16 . Previous studies have demonstrated equivalent outcomes to standard criteria organs with the use of livers from increased risk donors in adults and pediatrics 3,20 . In our analysis, we also demonstrated no difference in patient or allograft survival between recipients receiving PHS increased risk donors and non‐increased risk donors.…”
Section: Discussionsupporting
confidence: 46%
“…There is controversy regarding the use of donors who are considered “PHS increased risk.” 3 In 2004, the UNOS adopted the label “high risk donor” to identify donors that met the CDC 1994 criteria for high risk behavior for infection. In 2013, the PHS published updated guidelines for reducing HIV, HBV, and HCV transmission through organ transplantation 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although an extensive body of work has evaluated utilization of organs from IR donors among adults, little data exist in the context of pediatric patients. Wrenn et al examined utilization of IR kidneys for pediatric recipients in the early IR period (2004‐2008) showing no significant difference in allograft or patient survival, but lower acceptance rates for IR kidneys . Recent data have demonstrated that transplant outcomes using organs from IR donors are not different than standard donors for adults, yet organs from these donors are discarded at higher rates .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the opioid epidemic on organ transplantation has received significant attention, with a focus on the markedly increased 23 Recent data have demonstrated that transplant outcomes using organs from IR donors are not different than standard donors for adults, yet organs from these donors are discarded at higher rates. 4,24,25 Recent work has demonstrated pediatric recipients' decreasing access to high quality deceased donor kidneys post-Kidney Allocation System's transition to a KDPI-based allocation system.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study found that 42% of kidney transplant candidates would reject IRD kidneys under all circumstances (38). The reluctance to use IRD organs is perhaps even greater when treating pediatric transplant candidates, despite the fact that IRD kidneys are associated with similar allograft and patient survival and that only one unintended bloodborne pathogen transmission occurred in 8,000 unique pediatric transplants from 2008-2015 (39).…”
Section: Ird Kidneysmentioning
confidence: 99%